O Uso do método Jigsaw e de experimentos sensoriais na melhoria do ensino e aprendizagem de ácidos e bases no ensino médio - Florambel, Athus Torres (2019)
Aiming to connect the precepts of cooperative activity that assists students in the development of interpersonal skills, positive interdependence, individual responsibility, as well as the use of the motivating power of the experimental classes that arouse curiosity and instigate the students to the investigative process, is that it proposes to application of a teaching strategy that makes use of the cooperative learning method jigsaw, associated to sensory experiments involving the senses (taste, smell and vision). The research is carried out with high school students (3rd grade) from a state school in Maracanaú CE, on the subject of acids and bases. For the validation of the method will be used two semistructured questionnaires, one to analyze the contribu tions of the class in the proposed model to the learning of the subject acids and bases and another to analyze acceptance of the method, where the students expose their perceptions about the influence of the cooperative work in their learning, organization and relevance of the stages, didactic resources used and the topic addressed. The observed results show that the proposed class caused significant advances in the acquisition of knowledge by the students, about the theme addressed, and was very well accep ted, including reducing the resistance of students to perform reading activities. Therefore, it is concluded that combining different didactic methods with the teaching and learning process can result in an important instrument for stimulating students' le arning, with potential to accommodate the various forms of student learning.